Application of Three Weed Pathogenic Fungi on Bok choy (Brassica rapa subsp. chinnensis) (Department of Biology, Faculty of Mathematics and Sciences, Semarang State University . Ro, 2022)
Weed pathogenic fungi play an important role in biological control of weeds. Weeds grow a lot among cultivated plants, the role of weed pathogenic fungi to cultivated plants is not yet known. This research aimed to determine the effect of weed pathogenic fungi on bok choy. The research was carried out in Tambaksogra Village, Sumbang District, Banyumas Regency at an altitude of 100 m above sea level. Randomized block design was used with treatments of weed pathogenic fungi (Fusarium sp., Curvularia sp., Chaetomium sp., Fusarium sp. + Curvularia sp., Fusarium sp. + Chaetomium sp., Curvularia sp. + Chaetomium sp., and Fusarium sp. + Curvularia sp. + Chaetomium sp.) repeated four times. The observed variables included symptoms, incubation period, disease intensity, disease incidence, infection rate, AUDPC, number of leaves, plant height, and plant fresh and dry weight. Results showed that Weed pathogenic fungi of Curvularia sp. and Chaetomium sp. alone or in combination did not affect bok choy indicated by disease intensity of 0 %, and did not affect plant height, number of leaves, and plant fresh weight. The weed pathogenic fungi can be used as a bioherbicide in bok choy. To control weeds in bok choy plantations, both weed pathogenic fungi are recommended to be used. The further application of weed pathogenic fungi needs to be continued to other cultivated plants besides bokchoy.